Analysis of steel fibers pull-out. Experimental study - Isla Calderón, Facundo Andrés (2015)
A series of experimental pull-out tests consisting of different types of steel fibers with different inclinations extracted from various types of matrix is presented. Based on experimental results, the complete pull-out process including fiber and matrix failure modes is analyzed to obtain conclusions that could serve as basis for the development of a numerical model for fiber reinforced concrete including pull-out mechanism. The anchorage effect of the hook, the effect of fibers geometry and slenderness, fibers inclination and matrix type and strength are studied. It is shown that fiber inclination affects fibers pull-out strength and can lead to fiber breakage. The differences in fibers pull out response from concrete and mortar are assessed and justified. It is recommended performing pull-out tests from concrete to calibrate numerical models for fiber reinforced concrete and to take into account fibers inclinations in these models.